2004
DOI: 10.1002/sia.1698
|View full text |Cite
|
Sign up to set email alerts
|

Water formation from O2 and H2 on Rh tips: studies by field ion microscopy and pulsed field desorption mass spectrometry

Abstract: The catalytic oxidation of hydrogen on Rh tips was investigated using field ion microscopy and pulsed field desorption mass spectrometry (PFDMS). The reaction was carried out in the 10 −3 Pa range at 400-600 K.In a first series of experiments, emphasis was laid on revealing tip morphologies during the ongoing water formation. At a reaction temperature of 500 K, remarkable similarities with the previously studied pure oxygen case were found. Accordingly, a polyhedral tip shape with missing-row-type reconstructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 20 publications
(13 reference statements)
0
29
1
Order By: Relevance
“…1C. Previous atom-probe studies during the ongoing reaction have shown that this is due to the presence of Rh x O y indicating the formation of a surface oxide (12).…”
Section: Experimental Observationsmentioning
confidence: 85%
See 3 more Smart Citations
“…1C. Previous atom-probe studies during the ongoing reaction have shown that this is due to the presence of Rh x O y indicating the formation of a surface oxide (12).…”
Section: Experimental Observationsmentioning
confidence: 85%
“…Our system was examined through a series of micrographs between 400 and 550 K at a fixed oxygen pressure P O 2 and a varying hydrogen pressure P H 2 , which allows the catalytic formation of water to occur (11,12). In our experiments, it was concluded that for small P H 2 /P O 2 ratios the surface is predominantly covered by oxygen, whereas for large P H 2 /P O 2 ratios it is mainly covered by hydrogen (11).…”
Section: Experimental Observationsmentioning
confidence: 87%
See 2 more Smart Citations
“…For most conditions the NO + intensities are high and therefore contribute strongly, if not exclusively, to the image formation. In contrast to the H 2 -O 2 /Rh and Pt systems, where the produced water acts as the imaging species [28,29], only low amounts of water are detected under the experimental conditions corresponding to the H 2 -and NO-sides of the system (Fig. 4).…”
Section: Pulsed Field Desorption Mass Spectrometrymentioning
confidence: 94%